2022
DOI: 10.1371/journal.pone.0274892
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate population-level models informed by genetics predict more suitable habitat than traditional species-level model across the range of a widespread riparian tree

Abstract: Identifying and predicting how species ranges will shift in response to climate change is paramount for conservation and restoration. Ecological niche models are the most common method used to estimate potential distributions of species; however, they traditionally omit knowledge of intraspecific variation that can allow populations to respond uniquely to change. Here, we aim to test how population X environment relationships influence predicted suitable geographic distributions by comparing aggregated populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…All variables were the same spatial resolution (30 arc second; ~1 km at the Equator) and were projected into the same coordinate system (WGS1984) in ArcMap 59 . Based on a previous set of species distribution models built to describe the species’ range 60 , we selected a subset of the 27 available climatic variables. This is based on common practice of using expert judgment on the ecology of the taxa 61 to reduce multi-collinearity and over-fitting of models 62 .…”
Section: Methodsmentioning
confidence: 99%
“…All variables were the same spatial resolution (30 arc second; ~1 km at the Equator) and were projected into the same coordinate system (WGS1984) in ArcMap 59 . Based on a previous set of species distribution models built to describe the species’ range 60 , we selected a subset of the 27 available climatic variables. This is based on common practice of using expert judgment on the ecology of the taxa 61 to reduce multi-collinearity and over-fitting of models 62 .…”
Section: Methodsmentioning
confidence: 99%
“…Secondarily, it is also important to identify many of the barriers to broad inference in ecology and evolution. It is increasingly clear that integrating hierarchical genetic structure or phylogenetic structure is critical to the accuracy of results and scope of conclusions one can draw in most systems (Bayliss, Papeş, et al, 2022; Bayliss, Mueller, et al, 2022; Love et al, 2023; Read et al, 2016). Finally, it is important to develop new experimental frameworks that limit context‐dependent outcomes (Catford et al, 2021) and can be used to understand geographic variation in species interactions and feedbacks that drive ecosystem function (Van Nuland et al, 2016; Ware et al, 2019), as they related to fire disturbances.…”
Section: Moving Forwardmentioning
confidence: 99%
“…Over the last 20 years [55,56] it has become apparent that genetic structure needs to be incorporated in studies that estimate organismal responses to climate change to account for the influence of individual variation on the patterns and drivers of evolution and to control for non-independence among individuals and species. Over time, evidence demonstrating the critical importance of genetic variation in establishing broad inference across levels of organization has continued to grow [53,54]. However, the omission of data related to genetic structure is still common.…”
Section: Evolutionary History/genetic Hierarchymentioning
confidence: 99%
“…Phenotypic variation among species, or populations of a species, drives organismal responses to climate change [57]. Recent studies have clearly shown that the climatic drivers of species ranges and phenotypic variation vary depending upon whether or not genetic structure was incorporated into statistical models (for example, see bud break phenology in Populus species [54,58], and distribution and survival models in Pinus species [59]). More importantly, when species-level models were subsequently applied to populations within species, predictions of species responses to climate change varied by up to 50% compared to population specific models [59].…”
Section: Evolutionary History/genetic Hierarchymentioning
confidence: 99%
See 1 more Smart Citation